2018
DOI: 10.1039/c8tc02374c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bi2−2xSb2xS3 (0 ≤ x ≤ 1) solid solutions from solventless thermolysis of metal xanthate precursors

Abstract: Tris(O-ethylxanthate)bismuth(iii) (1) and tris(O-ethylxanthate)antimony(iii) (2) were synthesized and used as precursors for the preparation of Bi2−2xSb2xS3 alloys (x = 0, 0.2, 0.4, 0.6, 0.8 and 1) using melt reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 85 publications
1
26
0
Order By: Relevance
“…44,53 O'Brien et al synthesize Bi 2À2x Sb 2x S 3 solid solutions from solvent less thermolysis of metal xanthate precursors and showed a slight deviation from linearity in the energy band gap on Sb substitution due to stoichiometric variations in the synthesized solid solution. 54 The Raman spectra of the particles are shown in Fig. 11.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…44,53 O'Brien et al synthesize Bi 2À2x Sb 2x S 3 solid solutions from solvent less thermolysis of metal xanthate precursors and showed a slight deviation from linearity in the energy band gap on Sb substitution due to stoichiometric variations in the synthesized solid solution. 54 The Raman spectra of the particles are shown in Fig. 11.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…44,45 Additionally, by mixing different ratios of metal xanthates, doped metal sulfides with various transition metals can be resulted and several studies showed that such systems are very useful for controlling the optical, electrical and crystalline properties. [46][47][48] The metal xanthates are generally stable at room temperature and their decomposition typically occurs thermally via a mechanism known as Chugaev elimination. 24 However, it is also possible to decompose them chemically with the use of primary amines at room temperature 49 as well as photochemically with UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The method avoids the use of long chain capping ligands, and thus offers the possibility of synthesizing nanomaterials with abundant exposed active sites for enhanced electrocatalytic performance 43,44 . Various single source precursors such as metal thiolates, metal salts of dithiocarbamates, xanthates, thiocarboxylates and thiotetrazoles have been employed in the synthesis of a variety of nanostructured materials [45][46][47][48] . In this work, we have employed the solventless approach to synthesize nickel sulfide using nickel xanthate complexes as single source precursors.…”
mentioning
confidence: 99%